Zagadki w dawnej Europie : na tropach tajemniczych linii / DcErich von Daniken ; tlumaczyla Malgorzata Gawlik. - Daniken, Erich von, 1935-; Gawlik, Malgorzata (Wesola : Wydawnictwo Prokop, 2000)
Polish translation of "Ratsel im Alten Europa". A study of ancient civilizations of Europe and the possibility of extraterrestrial influences.
Includes bibliographical references (p. 141-[142])
Keywords: Civilization, Ancient -- Extraterrestrial influences